The Need for The Formation of a Culture of Teenage Students 'Use of The Media - Rakhimova Gulbahor Valijonovna (Zien Journals, 2022)
This article highlights the important aspects that make it necessary to shape the culture of adolescent students' use of the media.
Keywords: Media; information analysis; useful information; intellectual thinking